Downregulation of DmMANF in Glial Cells Results in Neurodegeneration and Affects Sleep and Lifespan in Drosophila melanogaster - Walkowicz, Lucyna; Kijak, Ewelina; Krzeptowski, Wojciech; Górska-Andrzejak, Jolanta; Stratoulias, Vassilis; Woznicka, Olga; Chwastek, Elzbieta; Heino, Tapio I.; Pyza, Elzbieta M. (Frontiers in Neuroscience, 2017)
In Drosophila melanogaster, mesencephalic astrocyte-derived neurotrophic factor (DmMANF) is an evolutionarily conserved orthologue of mammalian MANF and cerebral dopamine neurotrophic factor (CDNF), which have been shown to promote the survival of dopaminergic neurons in the brain. We observed especially high levels of DmMANF in the visual system of Drosophila, particularly in the first optic neuropil (lamina). In the lamina, DmMANF was found in glial cells (surface and epithelial glia), photoreceptors and interneurons. Interestingly, silencing of DmMANF in all neurons or specifically in photoreceptors or L2 interneurons had no impact on the structure of the visual system. However, downregulation of DmMANF in glial cells induced degeneration of the lamina. Remarkably, this neurodegeneration in the form of holes and/or tightly packed membranes was observed only in the lamina epithelial glial cells. Those membranes seem to originate from the endoplasmic reticulum, which forms autophagosome membranes. Moreover, capitate projections, the epithelial glia invaginations into photoreceptor terminals that are involved in recycling of the photoreceptor neurotransmitter histamine, were less numerous after DmMANF silencing either in neurons or glial cells. The distribution of the alpha subunit of Na+/K+-ATPase protein in the lamina cell membranes was also changed. At the behavioural level, silencing of DmMANF either in neurons or glial cells affected the daily activity/sleep pattern, and flies showed less activity during the day but higher activity during the night than did controls. In the case of silencing in glia, the lifespan of flies was also shortened. The obtained results showed that DmMANF regulates many functions in the brain, particularly those dependent on glial cells.